Evidence of a 2D Fermi surface due to surface states in a p-type metallic Bi2Te3. (10th April 2018) - Shrestha, K; Marinova, V; Lorenz, B; Chu, C W
Abstract: We present a systematic quantum oscillations study on a metallic, p -type Bi2 Te3 topological single crystal in magnetic fields up to B   =  7 T. The maxima/minima positions of oscillations measured at different tilt angles align to one another when plotted as a function of the normal component of magnetic field, confirming the presence of the 2D Fermi surface. Additionally, the Berry phase, β   =  0.4  ±  0.05 obtained from the Landau level fan plot, is very close to the theoretical value of 0.5 for the Dirac particles, confirming the presence of topological surface states in the Bi2 Te3 single crystal. Using the Lifshitz–Kosevich analyses, the Fermi energy is estimated to be meV, which is lower than that of other bismuth-based topological systems. The detection of surface states in the Bi2 Te3 crystal can be explained by our previous hypothesis of the lower position of the Fermi surface that cuts the 'M'-shaped valence band maxima. As a result, the bulk state frequency is shifted to higher magnetic fields, which allows measurement of the surface states signal at low magnetic fields.